The Joint Impact of Co-occupants and Co-defendants’ Criminal Behavior on Adolescents’ Criminal Behavior: a Cross-Lagged Analysis - Wientjes, Jacqueline (Crime & delinquency, 2023)
The present study investigated the joint impact of co-occupants and codefendants criminal behavior on adolescent criminal behavior using official Dutch police records. Co-occupant and co-defendant criminal behavior were used as proxies for family and peer criminal behavior, respectively. Data spanning 8 years (2010?2017) were analyzed from 56,802 adolescents, their co-occupants and co-defendants. Cross-lagged analyses were used to investigate prospective effects of co-occupant and co-defendant delinquency on adolescent delinquency. For males, prospective effects were found of co-defendant on adolescent delinquency violent offences, violent property offences, and nonviolent property offences. For females, prospective effects of co-defendants? delinquency were found for nonviolent property offences. Our findings underscore that having co-defendants with delinquent behavior is an important risk factor for delinquent activities in adolescence.